Development of poly(L-lactide) (PLLA) microspheres precipitated from triacetin for application in powder bed fusion of polymers - Dechet, Maximilian; Demina, Anna; Römling, Lea; Gomez Bonilla, Juan Sebastian; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2020)
In this work, the development and processing behavior of poly(L-lactide) (PLLA) particles for powder bed fusion (PBF) of polymers obtained via a green and sustainable process route are thoroughly studied. Liquid-liquid phase separation and precipitation from triacetin, a non-toxic solvent, are applied for the production of highly spherical PLLA particles of excellent flowability. Starting from the measured cloud-point diagram of the PLLA-triacetin system, appropriate temperature profiles for the precipitation process are derived. The effect of process parameters on the product properties is addressed in detail; the PLLA particles are characterized regarding their size distribution and morphology. Furthermore, material properties including thermal behavior (c.f. processing window for powder bed fusion (PBF)) and powder flowability are assessed. The spherical PLLA particles of narrow size distribution display a wide sintering window of 59 K and an excellent flowability due to the intrinsic surface roughness of the particles. Thus, tensile test bars and complex porous gyroid specimens were successfully manufactured via PBF without the need for any additional surface functionalization of the particles with flow agents. The high potential of the newly developed PLLA powders produced via an environmentally friendly approach omitting the use of halogenated or toxic solvents, as well as flowing aids, is demonstrated by mechanical testing of the printed specimen